Return Policy of E-retailers: An Extensive Review - TYAGI, VIKRAM; DHINGRA, VAISHALI (The journal of contemporary issues in business and government, 2021)
Selling a product is not the sole proposition of any e-retailer. Equally important is the number of issues involved in managing returns, chalking out a strong return policy so as to retain the customers. The problem with a number of e-retailers remains that they focus on one time sale of the product which leads to dissatisfaction among the customers. The forward and reverse logistics network of a company facilitate in improving its sales and image among the customers. Logistics services also lead to an enhancement in the confidence and trust of the consumers in the company and motivate them to make repeat purchases from such e-retailers. With ever-increasing competition in e-retailing, the onus on companies has also increased. They have to provide ample opportunity to the customer for getting satisfied and after that further wait for the return time limit to get over. The customer might reject a product on the grounds of being defective or simply because he didn’t liked it or found a better price deal somewhere else or has changed the mind. In either of these cases, most companies prefer to accept the returns because marketing believes in the age-old adage “customer is the king”. The return policy defines ground rules for product rejections by customers. A problematic return policy may drive away customers, whereas too easy policy may encourage unjustified product rejections. Therefore, E-retailers have to make a strategic balance is designing their return policies. This review paper is based on the return policies of some of the popular e-retailers and also the importance of ‘returns’ in case of e-retailing business. Further, various review papers related to the impact of the return policy on consumers’ online shopping behaviour have been analysed and have been made a part of this review paper. A conceptual framework based on the impact of the return policy of e-retailers on consumers’ buying behaviour and the mediating effect of knowledge, awareness and attitude of consumers’ towards online shopping behaviour on the relationship between the impact of the return policy of e-retailers on consumers’ buying behaviour has been suggested on which empirical research can be carried out in the future.